Emotional Maturity Correlates with Marriage Readiness in Early Adult Women: Kematangan Emosional Berkorelasi dengan Kesiapan Menikah pada Wanita Dewasa Awal - Intan Wuri Kiranasari; Ririn Dewanti Dian Samudra Indriani (Academia Open, 2025)
General Background: Marriage represents a major developmental milestone in early adulthood that requires psychological, social, and physiological preparedness. Specific Background: Early adult women often experience concerns related to financial stability, lifestyle changes, communication adjustment, and family responsibilities prior to marriage, highlighting the importance of psychological readiness. Emotional maturity is considered an essential personal capacity that supports emotional regulation, objective thinking, responsibility, and resilience when facing relational challenges. Knowledge Gap: Empirical evidence examining the association between emotional maturity and marriage readiness among early adult women within community-based Indonesian populations remains limited. Aims: This study aimed to determine and analyze the relationship between emotional maturity and marriage readiness among early adult women in Kalisampurno Village, Tanggulangin, Sidoarjo. Results: Using a quantitative correlational design, data were collected from 191 early adult women selected through accidental sampling. Data analysis using Pearson product-moment correlation demonstrated a significant positive relationship between emotional maturity and marriage readiness (r = 0.611, p < 0.05), with R square of 0.373 indicating that emotional maturity contributed 37.3% of marriage readiness variance. Categorization analysis showed most participants were within the moderate category for emotional maturity (38%) and marriage readiness (36%). Novelty: This study provides quantitative community-based evidence demonstrating a strong association between emotional maturity and marriage readiness among early adult women in a local Indonesian context. Implications: The findings support the need for premarital education, counseling programs, and family support systems that focus on emotional development to prepare early adult women for marital roles and responsibilities. Highlights: Emotional Regulation Capacity Accounted for 37.3 Percent of Readiness Variance. Majority of Participants Demonstrated Moderate Psychological Preparation Levels. Statistical Testing Revealed a Strong Positive Association Between Both Measured Variables. Keywords: Emotional Maturity, Marriage Readiness, Early Adult Women, Correlational Study, Premarital Preparation